Alterations at the blood-brain barrier and brain parenchyma along brain metastasization of breast cancer - Santos, Tânia Custódio (2019)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2016